2009
DOI: 10.1105/tpc.109.070078
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Decapping 5 Is Required for mRNA Decapping, P-Body Formation, and Translational Repression during Postembryonic Development

Abstract: Eukaryotic processing bodies (P-bodies) are implicated in mRNA storage and mRNA decapping. We previously found that a decapping complex comprising Decapping 1 (DCP1), DCP2, and Varicose in Arabidopsis thaliana is essential for postembryonic development, but the underlying mechanism is poorly understood. Here, we characterized Arabidopsis DCP5, a homolog of human RNA-associated protein 55, as an additional P-body constituent. DCP5 associates with DCP1 and DCP2 and is required for mRNA decapping in vivo. In spit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
205
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(229 citation statements)
references
References 33 publications
8
205
0
2
Order By: Relevance
“…1C). Cordycepin treatments were effective in rice in blocking transcription, as evidenced by the reduced half-lives of EXPL2 (AK068088) and SEN1 (AK120910), rice homologs of Arabidopsis genes that produce very unstable mRNAs (Gutierrez et al, 2002;Lidder et al, 2005;Xu and Chua, 2009), under normal growth conditions (Supplemental Fig. S5).…”
Section: Smd Of Photosynthetic Genes During Stress Conditionsmentioning
confidence: 99%
“…1C). Cordycepin treatments were effective in rice in blocking transcription, as evidenced by the reduced half-lives of EXPL2 (AK068088) and SEN1 (AK120910), rice homologs of Arabidopsis genes that produce very unstable mRNAs (Gutierrez et al, 2002;Lidder et al, 2005;Xu and Chua, 2009), under normal growth conditions (Supplemental Fig. S5).…”
Section: Smd Of Photosynthetic Genes During Stress Conditionsmentioning
confidence: 99%
“…DCP5 is a component of the decapping complex, but it does not promote the decapping activity, whereas DCP1 and VCS do. 45 The distinct functions in decapping of DCP1, DCP2 and VCS, independent from DCP5, may cause the decrease in miRNA levels in dcp1, dcp2 and vcs mutants. However, because dcp5-1 is a knockdown mutant, we need to determine if the miRNA accumulation decreases in the dcp5 knockout mutant.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It was previously reported that DCP5 interacts with DCP1, DCP2 and VCS in the P-body, and plays a role in the decapping in vivo. 45 To confirm whether this decapping co-activator is involved in miRNAs and siRNA accumulation, we examined the accumulation of miRNAs and siRNA in dcp5-1, a dcp5-impaired mutant. Unlike in dcp1-1, dcp2-1 and vcs-6 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…First, scd6Δ strains show a synthetic defect in decapping with the edc3Δ 44 (Edc3 is another related activator of decapping). 43 Second, Scd6, Dcp5 (Arabidopsis ortholog of Scd6) and the S. pombe Scd6 physically interact with purified Dcp2 but do not stimulate its decapping activity, 45,46 A final implication of this work and one from other labs is that eIF4G could be an integrator of functional states of mRNA. eIF4G can provide a scaffold to recruit proteins that negatively affect translation, such as RGG motif proteins, 1 Khd1 20 and L13a.…”
Section: Why Do So Many Rgg Motifmentioning
confidence: 99%